Linking Hr Flexibility and Employee Competence to Employee Performance in Organizations - Marshall Alfayed Mahasari; Marwan Man Soleman; Adnan Rajak; Alfi Syahri Rilafani Hanafi; Al Ama Asyahrul (Journal of International Conference Proceedings, 2025)
This study examines the effect of human resource flexibility and employee competence on employee performance at PT Pos Indonesia, Ternate Branch. In the increasingly competitive postal and logistics industry, organizations must adopt adaptive and competency-based human resource management. This research used a causal quantitative approach with 45 permanent employees as respondents, employing a structured questionnaire measured on a five-point Likert scale. Data were analyzed using multiple linear regression through SPSS version 25. The results showed that human resource flexibility has a positive and significant effect on employee performance, whereas employee competence does not have a significant impact. These findings suggest that adaptability and behavioral flexibility are stronger determinants of performance than individual competence in a bureaucratic public organization. This study contributes to human resource management literature by highlighting the strategic role of HR flexibility in enhancing employee performance within government-linked institutions.